Electrolyte, battery, energy storage device and energy storage system

By adding azaindole additives to the electrolyte of lithium-ion batteries, a nitrogen-rich SEI film was constructed, which solved the problem of low retention of circulation capacity of lithium-ion batteries at high temperatures, and significantly improved the high-temperature circulation performance of the battery. .

CN119481284APending Publication Date: 2025-02-18XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411670555.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

现有的锂离子电池在高温下的循环容量保持率较低,宽温长寿命性能较差。

Method used

An electrolyte containing azaindole additive is used, which can reduce the surface of the negative electrode active layer of the negative electrode sheet to construct a nitrogen-rich SEI film to improve the high temperature tolerance of the SEI film.

Benefits of technology

通过构建更稳定的SEI膜,提高了电池的高温循环性能,降低了SEI膜在高温下的溶解度,使电池在高温条件下具有更好的循环容量保持率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481284A_ABST
    Figure CN119481284A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte, a battery, an energy storage device and an energy storage system. The electrolyte provided by the embodiment of the invention comprises electrolyte salt and a first additive, wherein the first additive is an azaindole additive. When the electrolyte provided by the embodiment of the invention is applied to the battery, the battery can have relatively high high-temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and specifically to an electrolyte, a battery, an energy storage device and an energy storage system. Background Art

[0002] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion batteries have been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and their application range is becoming more and more extensive.

[0003] With the development of the energy storage industry, higher requirements are placed on the life attenuation and service life of lithium-ion batteries. However, the existing lithium-ion batteries have a low cycle capacity retention rate at high temperatures. Summary of the invention

[0004] The embodiment of the present application provides an electrolyte, which, when applied to a battery, can enable the battery to have higher high-temperature cycle performance.

[0005] In a first aspect, an embodiment of the present application provides an electrolyte, wherein the electrolyte includes an electrolyte salt and a first additive, wherein the first additive is an azaindole additive.

[0006] In some embodiments, the azaindole additive comprises at least one of the following structural formulas:

[0007]

[0008] Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0009] R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0010] R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0011] R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0012] R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0013] R6 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0014] R7 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0015] R8 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0016] R9 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0017] R 10 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0018] R 11 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0019] R 12 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0020] R 13 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0021] R 14 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0022] R 15 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0023] R 16 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0024] R 17 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0025] R 18 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0026] R 19 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0027] R 20 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0028] R 21 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0029] R 22is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0030] R 23 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0031] R 24 It is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl and vinyl.

[0032] In some embodiments, the azaindole additive has a substituent, and the substituent includes at least one of an electron-withdrawing group, a silicon-containing group, and a reactive group.

[0033] In some embodiments, the azaindole additive comprises at least one of the following structural formulas:

[0034]

[0035] In some embodiments, the electrolyte further includes a second additive, and the second additive includes at least one of a cyclic carbonate additive and a cyclic sulfate additive.

[0036] In some embodiments, the mass ratio A of the first additive to the second additive is in the range of 0.1≤A≤1.5.

[0037] In some embodiments, in the electrolyte, the mass fraction a of the first additive is in the range of 0.05%≤a≤3.0%.

[0038] In some embodiments, in the electrolyte, the mass fraction b of the second additive is in the range of 1%≤b≤4%.

[0039] In a second aspect, an embodiment of the present application further provides a battery, comprising:

[0040] The electrolyte described in the embodiment of the present application;

[0041] A positive electrode sheet, the positive electrode sheet is immersed in the electrolyte;

[0042] a diaphragm, located on one side of the positive electrode plate and immersed in the electrolyte, and

[0043] A negative electrode plate is disposed on a side of the diaphragm away from the positive electrode plate and immersed in the electrolyte.

[0044] In a third aspect, an embodiment of the present application further provides an energy storage device, comprising:

[0045] The housing; and

[0046] A plurality of batteries according to the second aspect of the present application are contained in the box.

[0047] In a fourth aspect, an embodiment of the present application further provides an energy storage system, which includes:

[0048] The energy storage device described in the third aspect of the present application; and

[0049] An electric energy conversion device, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.

[0050] The electrolyte of the embodiment of the present application includes an electrolyte salt and a first additive, wherein the first additive is an azaindole additive. The azaindole additive contains nitrogen (N element), which can preferentially undergo a reduction reaction on the surface of the negative electrode active layer of the negative electrode plate, thereby decomposing on the surface of the negative electrode active layer and constructing a SEI film rich in nitrogen. The SEI film rich in nitrogen has better high temperature tolerance, thereby better reducing the solubility of the SEI film at high temperature, making the SEI film more stable at high temperature, and thus improving the high temperature cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0052] Figure 1 It is a structural block diagram of an energy storage system according to an embodiment of the present application.

[0053] Figure 2 This is an application scenario diagram of an energy storage system according to an embodiment of the present application.

[0054] Figure 3 It is a schematic structural diagram of an energy storage device according to an embodiment of the present application.

[0055] Figure 4 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.

[0056] Figure 5 The battery of one embodiment of the present application is Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.

[0057] Figure 6 The positive electrode sheet of one embodiment of the present application is Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.

[0058] Figure 7 The negative electrode of one embodiment of the present application is along the Figure 4 Schematic diagram of the cross-sectional structure in the AA direction.

[0059] Description of reference numerals:

[0060] 100 -battery, 110 -positive electrode plate, 111 -positive current collector, 112 -positive electrode active layer, 120 -diaphragm, 130 -negative electrode plate, 131 -negative current collector, 132 -negative electrode active layer, 140 -housing, 150 -end cover assembly, 141 -receiving chamber, 200 -energy storage device, 210 -casing, 300 -energy storage system, 310 -electric energy conversion device. DETAILED DESCRIPTION

[0061] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0062] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0063] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0064] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.

[0065] At present, the generation of green electricity generally relies on photovoltaics, wind power, and hydropower, etc. However, wind and solar energy generally have problems of strong intermittency and large volatility, which will cause instability in the power grid, insufficient electricity during peak hours, and too much electricity during valley hours. Unstable voltage will also cause damage to electricity. Therefore, insufficient electricity demand or insufficient grid acceptance capacity may cause the problem of "abandoning wind and solar power". To solve these problems, we must rely on energy storage. That is, converting electrical energy into other forms of energy through physical or chemical means and storing it, and converting energy into electrical energy and releasing it when needed. In simple terms, energy storage is like a large "power bank". When photovoltaic and wind energy are sufficient, electrical energy is stored and the stored electricity is released when needed.

[0066] The current energy storage (i.e., energy storage) application scenarios are relatively broad, including power generation side energy storage, grid side energy storage, and power consumption side energy storage. The following uses power generation side energy storage as an example to describe the energy storage system of the embodiment of the present application in detail, which should not be understood as a limitation on the energy storage system of the embodiment of the present application.

[0067] See also Figure 1 and Figure 2 The embodiment of the present application also provides an energy storage system 300, which includes: an electric energy conversion device 310 and the energy storage device 200 described in the embodiment of the present application, the electric energy conversion device 310 is electrically connected to the energy storage device 200, the electric energy conversion device 310 is used to convert other forms of energy into electric energy, and the energy storage device 200 is used to store the electric energy.

[0068] Optionally, the electric energy conversion device 310 can convert at least one other form of energy such as solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0069] Optionally, the number of the electric energy conversion devices 310 may be one or more. When there are multiple electric energy conversion devices 310, the multiple electric energy conversion devices 310 may be connected in series, in parallel, or in mixed connection, which is not specifically limited in the present application.

[0070] Optionally, the electric energy conversion device 310 may be, but is not limited to, at least one of a photovoltaic panel, a wind power generation device, a hydropower generation device, and the like.

[0071] Optionally, the number of the energy storage devices 200 may be one or more. When the number of the energy storage devices 200 is multiple, the multiple energy storage devices 200 are connected in series or in parallel, which is not specifically limited in the present application.

[0072] When working, the power conversion device 310 is used to convert other forms of energy into electrical energy and store it in the energy storage device 200. The electrical energy stored in the energy storage device 200 can be supplied to electrical loads such as street lamps and household appliances for use when the electricity price is at a peak, or to supply power when the power grid is out of power. The electrical energy generated by the power conversion device 310 can also be supplied to the power grid through high-voltage cables to alleviate the power supply pressure of the power grid during peak hours.

[0073] See also Figure 3 The embodiment of the present application further provides an energy storage device 200 , which includes a box 210 and a plurality of batteries 100 , wherein the plurality of batteries 100 are stacked and accommodated in the box 210 .

[0074] The term "plurality" means greater than or equal to two.

[0075] It can be understood that the multiple batteries 100 of the energy storage device 200 can be connected in parallel with each other; or in series with each other; or partially in parallel and partially in series (in other words, mixed connection). This application does not make any specific restrictions on the connection method of multiple batteries 100 of the same energy storage device 200.

[0076] Optionally, the energy storage device may be at least one of a small energy storage box, a large energy storage cabinet, an energy storage module, etc. The present application does not specifically limit the form of the energy storage device. The form of the energy storage device of the present application is only one of its many forms and should not be understood as a limitation on the energy storage device of the present application.

[0077] It can be understood that the box body 210 has a receiving cavity, and multiple batteries 100 are received in the receiving cavity. In some embodiments, each receiving cavity receives one battery 100. In other embodiments, each receiving cavity receives multiple batteries 100.

[0078] Optionally, the battery 100 is but not limited to at least one of a lithium ion battery, a sodium ion battery, etc. In the description of the embodiments of the present application, the lithium ion battery is used as an example, which should not be understood as a limitation on the battery 100 and the electrolyte of the embodiments of the present application.

[0079] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion batteries have been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and their application range is becoming more and more extensive.

[0080] With the development of the energy storage industry, higher requirements are placed on the life attenuation and service life of lithium-ion batteries. However, the existing lithium-ion batteries have a low cycle capacity retention rate at high temperatures and poor wide temperature and long life performance.

[0081] Battery degradation is mainly caused by the reaction of lithium ions on the surface of the negative electrode of the battery. First, during charging, ester solvents are easily reduced on the surface of the low-potential negative electrode and react with lithium, thereby consuming active lithium; secondly, the negative active layer of the negative electrode is constantly expanding and shrinking during the process of lithium extraction, causing the solid electrolyte interface membrane (SEI) on the surface of the negative active layer to be constantly pulled, exposing a new interface that continuously reacts with the electrolyte, resulting in the loss of active lithium. At high temperatures, the reaction between the surface of the negative electrode and the electrolyte is further intensified, and the interface stability of the negative electrode is further reduced, which greatly reduces the high-temperature cycle performance of the battery.

[0082] See also Figure 4 and Figure 5 The embodiment of the present application provides a battery 100, which includes an electrolyte, a positive electrode plate 110, a separator 120 and a negative electrode plate 130, wherein the separator 120 is located on one side of the positive electrode plate 110; the negative electrode plate 130 is arranged on the side of the separator 120 away from the positive electrode plate 110.

[0083] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 are at least partially immersed in the electrolyte.

[0084] It can be understood that the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly. The electrode assembly can be, but is not limited to, a winding structure, a laminated structure, etc., which is not specifically limited in the present application.

[0085] It should be noted that the positive electrode sheet 110 and the negative electrode sheet 130 may be collectively referred to as electrode sheets. In other words, the electrode sheets include the positive electrode sheet 110 and the negative electrode sheet 130 .

[0086] See also Figure 6 Optionally, the positive electrode sheet 110 includes a positive current collector 111 and a positive active layer 112, and the positive active layer 112 is disposed on the surface of the positive current collector 111. It can be understood that the positive active layer 112 can cover one surface or two opposite surfaces of the positive current collector 111.

[0087] Optionally, the positive electrode current collector 111 may be, but is not limited to, an aluminum sheet.

[0088] Optionally, the positive electrode active layer 112 includes a positive electrode active material, a positive electrode conductor, a positive electrode binder and a positive electrode thickener.

[0089] Optionally, the positive electrode active material may be, but is not limited to, lithium iron phosphate.

[0090] Optionally, the positive electrode conductive agent may be, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.

[0091] Optionally, the positive electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene butadiene rubber (SBR).

[0092] Optionally, in the positive electrode active layer 112, the mass fraction of the positive electrode binder ranges from 2wt% to 4wt%. Specifically, in the positive electrode active layer 112, the mass fraction of the positive electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the positive electrode binder is too small, the positive electrode active layer 112 is prone to pulverization or slag; if the mass fraction of the positive electrode binder is too large, the energy density of the positive electrode sheet 110 is reduced.

[0093] Optionally, the positive electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).

[0094] Optionally, the diaphragm 120 may be, but is not limited to, at least one of a polypropylene film (PP film for short), a polyethylene film (PE film for short), a ceramic diaphragm 120 , and the like.

[0095] Optionally, the thickness of the diaphragm 120 is 14 μm to 18 μm. Specifically, the thickness of the diaphragm 120 may be, but is not limited to, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, etc.

[0096] See also Figure 7 Optionally, the negative electrode sheet 130 includes a negative electrode current collector 131 and a negative electrode active layer 132, and the negative electrode active layer 132 is disposed on the surface of the negative electrode current collector 131. It can be understood that the negative electrode active layer 132 can cover one surface or two opposite surfaces of the negative electrode current collector 131.

[0097] Optionally, the negative electrode current collector 131 may be, but is not limited to, a copper sheet.

[0098] Optionally, the negative electrode active layer 132 includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a negative electrode thickener.

[0099] Optionally, the negative electrode active material may be, but is not limited to, graphite.

[0100] Optionally, the negative electrode conductive agent may be, but is not limited to, at least one of conductive carbon black (SP for short), acetylene black, carbon nanotubes, carbon fibers, graphene, and the like.

[0101] Optionally, the negative electrode binder may be, but is not limited to, at least one of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyhexafluoropropylene, styrene-butadiene rubber, and the like.

[0102] Optionally, in the negative electrode active layer 132, the mass fraction of the negative electrode binder ranges from 2wt% to 4wt%. Specifically, in the negative electrode active layer 132, the mass fraction of the negative electrode binder may be, but is not limited to, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, etc. If the mass fraction of the negative electrode binder is too small, the negative electrode active layer 132 is prone to pulverization or slag; if the mass fraction of the negative electrode binder is too large, the energy density of the negative electrode plate 130 is reduced.

[0103] Optionally, the negative electrode thickener may be, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC for short), polyacrylamide (PAM) and polymethacrylate (PMA).

[0104] Please see again Figure 4 and Figure 5 Optionally, the battery 100 further includes a shell 140 and an end cover assembly 150 , wherein the shell 140 and the end cover assembly 150 enclose a receiving cavity 141 , and the receiving cavity 141 is used to receive the electrolyte, the positive electrode plate 110 , the diaphragm 120 and the negative electrode plate 130 .

[0105] The embodiment of the present application further provides an electrolyte, which includes an electrolyte salt and a first additive, wherein the first additive is an azaindole additive.

[0106] After the battery 100 is assembled, it needs to go through a formation process before use. Battery 100 formation is an important step in the battery 100 production process. The battery 100 is charged and discharged by a special battery 100 formation device to ensure that the battery 100 achieves the specified service life. The formation process requires high-precision voltage and current control to ensure the quality and performance of the battery 100. This process usually includes a negative electrode reduction reaction during the first charge to form a stable solid electrolyte interface film (SEI film) to prevent the irreversible consumption of electrolyte and lithium ions.

[0107] The formation of the lithium-ion battery 100 is a complex process, the main purpose of which is to activate the active materials of the battery 100. In the lithium-ion battery 100, the formation involves the formation of the SEI film. The SEI film is a thin film formed on the interface between the negative electrode active layer 132 and the electrolyte, which can protect the negative electrode active layer 132 and prevent the electrolyte from decomposing. The formation of the SEI film is an irreversible chemical reaction process, which consumes lithium ions and increases the resistance of the positive electrode plate 110 / electrolyte interface and the negative electrode plate 130 / electrolyte interface. Once the SEI film is formed, the battery 100 can be subjected to multiple charge and discharge cycles.

[0108] The electrolyte of the embodiment of the present application includes an electrolyte salt and a first additive, wherein the first additive is an azaindole additive. The azaindole additive contains nitrogen (N element), which can preferentially undergo a reduction reaction on the surface of the negative electrode active layer 132 of the negative electrode plate 130, thereby decomposing on the surface of the negative electrode active layer 132 and constructing a SEI film rich in nitrogen. The SEI film rich in nitrogen has better high temperature tolerance, thereby better reducing the solubility of the SEI film at high temperature, making the SEI film more stable at high temperature, thereby improving the high temperature cycle performance (i.e., high temperature cycle capacity retention rate) of the battery 100.

[0109] In some embodiments, the azaindole additive comprises at least one of the following structural formulas:

[0110]

[0111] Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0112] R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0113] R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0114] R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0115] R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0116] R6 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0117] R7 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0118] R8 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0119] R9 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0120] R 10 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0121] R 11 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0122] R 12 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0123] R 13 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0124] R 14 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0125] R 15 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0126] R 16 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0127] R 17 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0128] R 18 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0129] R 19 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0130] R 20is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0131] R 21 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0132] R 22 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0133] R 23 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl;

[0134] R 24 It is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl and vinyl.

[0135] The azaindole additive of the structure of this embodiment can better construct a nitrogen-rich SEI film on the surface of the negative electrode active layer 132, thereby better improving the high temperature tolerance of the SEI film, better reducing the solubility of the SEI film at high temperature, making the SEI film more stable at high temperature, and thus improving the high temperature cycle performance of the battery 100. In addition, compared with 4-azaindole, 5-azaindole and 7-azaindole, 7-azaindole has a stronger coordination ability and can participate in the lithium ion (Li + )'s solvated structure is more likely to migrate to the surface of the negative electrode active layer 132 to undergo a reduction reaction; furthermore, the SEI interface film constructed by 7-azaindole can reduce the side reactions at the SEI interface during the cycle process, reduce the consumption of active lithium, and thus further improve the cycle performance of the battery 100.

[0136] In some embodiments, the azaindole additive has a substituent, and the substituent includes at least one of an electron-withdrawing group, a silicon-containing group, and a reactive group.

[0137] Optionally, the electron-withdrawing group may be, but is not limited to, a fluorine-containing substituent. Optionally, the fluorine-containing substituent may be, but is not limited to, one of fluorine (-F), trifluoromethyl (-CF3), etc. The electron-withdrawing group may reduce the lowest unoccupied molecular orbital (LUMO energy level) of the azaindole additive, thereby increasing the reduction potential of the azaindole additive, so that the azaindole additive preferentially reacts at the cross section of the negative electrode active layer 132 and participates in the construction of the SEI film; in addition, the azaindole additive containing a fluorine substituent may increase the LiF component in the SEI film, thereby further reducing the solubility of the SEI film in the electrolyte, improving the thermal stability and acid resistance of the SEI film, and thereby improving the high temperature cycle performance of the battery 100.

[0138] Optionally, the silicon-containing group may be, but is not limited to, a trimethylsilyl group. The side reactions of the battery 100 increase at high temperatures, and the acid production also increases. The azaindole additive containing the silicon group may react with HF in the electrolyte to remove the free acid in the electrolyte, thereby preventing the free acid from damaging the SEI film, improving the stability of the SEI film, and thus improving the high-temperature cycle performance of the battery 100.

[0139] Optionally, the reactive group may be but is not limited to a vinyl group, which may participate in the reaction of the SEI film, thereby increasing the degree of polymerization of organic components in the SEI film, so that the organic components in the SEI film can withstand higher temperatures, thereby increasing the thermal stability of the SEI film, reducing the solubility of the SEI film in the electrolyte, and improving the cycle performance of the battery 100.

[0140] In some embodiments, the azaindole additive comprises at least one of the following structural formulas:

[0141]

[0142] The azaindole additive of the structure of this embodiment can better construct a nitrogen-rich SEI film on the surface of the negative electrode active layer 132, thereby better improving the high temperature tolerance of the SEI film, better reducing the solubility of the SEI film at high temperature, making the SEI film more stable at high temperature, and thus improving the high temperature cycle performance of the battery 100. In addition, compared with 4-azaindole, 5-azaindole and 7-azaindole, 7-azaindole has a stronger coordination ability and can participate in the lithium ion (Li + )'s solvated structure is more likely to migrate to the surface of the negative electrode active layer 132 to undergo a reduction reaction; furthermore, the SEI interface film constructed by 7-azaindole can reduce the side reactions at the SEI interface during the cycle process, reduce the consumption of active lithium, and thus further improve the cycle performance of the battery 100.

[0143] In some embodiments, the electrolyte further includes a second additive, and the second additive includes at least one of a cyclic carbonate additive and a cyclic sulfate additive.

[0144] Optionally, the cyclic carbonate additive may include, but is not limited to, at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), 3,3,3-trifluoropropylene carbonate (TFPC), and the like.

[0145] Optionally, the cyclic sulfate additive may include, but is not limited to, at least one of diethylene sulfate (DTD), 1,3-propane sultone (PS), propenyl-1,3-sultone (PST), methylene methane disulfonate (MMDS), and the like.

[0146] In this embodiment, by using azaindole additives and cyclic carbonate additives, or azaindole additives and cyclic sulfate additives together, during the formation of the SEI film of the negative electrode active layer 132, the azaindole additives can copolymerize with the cyclic carbonate containing unsaturated bonds or promote the ring opening of the cyclic carbonate and the cyclic sulfate, further generate inorganic salts and organic polymers, improve the thermal stability of the SEI, and thus further improve the cycle performance of the battery 100. Compared with the solution of adding only the azaindole additive (the first additive) or only the second additive, adding the azaindole additive and the second additive at the same time can further improve the stability of the SEI film of the negative electrode active layer 132, thereby improving the high temperature cycle performance of the battery 100.

[0147] In some embodiments, in the electrolyte, the mass ratio A of the first additive to the second additive is in the range of 0.1≤A≤1.5.

[0148] Specifically, the mass ratio A of the first additive to the second additive in the electrolyte may be, but is not limited to, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 1.0, 1.2, 1.4, 1.5, etc.

[0149] In the present embodiment, when the mass ratio A of the first additive to the second additive is too small, the content of the azaindole additive in the electrolyte is too little, and the content of the nitrogen element in the SEI film of the negative electrode active layer 132 is insufficient, which reduces the thermal stability of the SEI film, thereby deteriorating the high temperature cycle performance of the battery 100, causing the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C to decrease; when the mass ratio A of the first additive to the second additive is too large, the SEI film of the negative electrode active layer 132 is mainly constructed by the azaindole additive, the polymer of the organic layer in the SEI film is reduced, and it is difficult to form a dense and thick SEI film, which makes the SEI film easily damaged, thereby causing the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C to decrease. When the mass ratio A of the first additive to the second additive is 0.1 to 1.5, when the SEI membrane of the battery 100 is constructed, the azaindoles preferentially undergo a reduction reaction, promoting the polymerization reaction of the cyclic carbonate additive or the cyclic sulfate additive, and forming an organic layer of the SEI membrane with a high degree of polymerization with the cyclic carbonate additive or the cyclic sulfate additive, thereby improving the thermal stability of the SEI and the high-temperature cycle performance of the battery 100.

[0150] In some embodiments, in the electrolyte, the mass fraction a of the first additive is in the range of 0.05%≤a≤3.0%.

[0151] It can be understood that in the electrolyte, the mass fraction a of the azaindole additive is in the range of 0.05%≤a≤3.0%.

[0152] Specifically, in the electrolyte, the mass fraction a of the first additive can be but is not limited to 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, 2.8%, 3.0%, etc.

[0153] In this embodiment, if the mass fraction a of the azaindole additive in the electrolyte is too low, the improvement in the heat resistance of the SEI film formed on the negative electrode plate 130 is limited, and the formed SEI film cannot effectively protect the negative electrode plate 130, which is not conducive to improving the high-temperature cycle performance of the battery 100; if the mass fraction a of the azaindole additive in the electrolyte is too high, the thickness of the SEI film formed on the surface of the negative electrode plate 130 is too thick, which reduces the kinetic performance of the battery 100, makes the battery 100 prone to lithium precipitation during the charge and discharge cycle, consumes active lithium, and in addition, increases the polarization of the battery 100, causes the loss of reversible lithium, and thus reduces the cycle performance of the battery 100.

[0154] Furthermore, in the electrolyte, the mass fraction a of the first additive is in the range of 0.3%≤a≤1.0%. This can better improve the heat resistance of the SEI film, improve the cycle capacity retention rate of the battery 100, and make the battery 100 have better dynamic performance, less prone to polarization, and less prone to lithium precipitation.

[0155] In some embodiments, in the electrolyte, the mass fraction b of the second additive is in the range of 1%≤b≤4%.

[0156] Specifically, the mass fraction b of the second additive in the electrolyte can be but is not limited to 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, 2.8%, 3.0%, 3.3%, 3.5%, 3.8%, 4%, etc.

[0157] In the present embodiment, in the electrolyte, if the mass fraction b of the second additive is too small, the polymer of the organic layer in the SEI film of the negative electrode active layer 132 of the battery 100 is relatively low, and it is difficult to form a dense and thick SEI film, so that the SEI film is easily damaged, thereby reducing the high temperature cycle performance of the battery 100; in the electrolyte, if the mass fraction b of the second additive is too large, the impedance of the SEI film of the battery 100 is too large, and the lithium insertion impedance is too large, so that the battery 100 is prone to lithium precipitation during the charge and discharge process, consuming active lithium. In addition, the polarization of the battery 100 is increased, resulting in the loss of reversible lithium, thereby reducing the cycle performance of the battery 100.

[0158] Optionally, the electrolyte salt is a lithium salt. The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorobis(oxalatophosphate) (LiODFP), lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonate (CF3SO3Li), etc.

[0159] Optionally, in the electrolyte, the total molar concentration M of the lithium salt is in the range of 0.7mol / L≤M≤1.4mol / L. In the electrolyte, the total molar concentration M of the lithium salt may be, but is not limited to, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, etc. If the total molar concentration M of the lithium salt is too small, the concentration of free ions in the electrolyte is too small, which reduces the conductivity of the electrolyte and thus reduces the kinetic performance of the battery 100; if the total molar concentration M of the lithium salt is too large, it is easy for a part of the electrolyte salt to be undissociated, and the viscosity of the electrolyte will increase, which in turn reduces the conductivity of the electrolyte and also reduces the kinetic performance of the battery 100. When the total molar concentration M of the lithium salt in the electrolyte is in the range of 0.7 mol / L≤M≤1.4 mol / L, the electrolyte can have a higher conductivity, so that the battery 100 has better kinetic performance.

[0160] In some embodiments, the electrolyte further includes a lithium salt additive. The lithium salt additive can supplement lithium ions in the electrolyte. In addition, the lithium salt additive can improve the impedance of the positive electrode plate 110 or the negative electrode plate 130 and improve the dynamic performance of the battery 100.

[0161] Optionally, in the electrolyte, the mass fraction w1 of the lithium salt additive is 0.2wt%≤w1≤2wt%. Specifically, the mass fraction w1 of the lithium salt additive may be, but is not limited to, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, etc. If the mass fraction w1 of the lithium salt additive is too small, the reduction of the impedance of the positive electrode sheet 110 or the negative electrode sheet 130 is limited, and it is difficult to increase the dynamic performance of the positive electrode sheet 110 or the negative electrode sheet 130; if the mass fraction w1 of the lithium salt additive is too large, due to the limited solubility of the lithium salt additive, when the concentration of the lithium salt additive reaches a certain level, the dynamic performance of the positive electrode sheet 110 or the negative electrode sheet 130 will not be improved, but the cost of the battery 100 will be greatly increased. When the mass fraction w1 of the lithium salt additive is 0.2wt%≤w1≤2wt%, the dynamic performance of the positive electrode sheet 110 or the negative electrode sheet 130 can be improved while the cost of the battery 100 can be lowered.

[0162] Optionally, the lithium salt additive includes at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiODFB), and lithium difluorooxalate phosphate. In this embodiment, the use of these lithium salt additives can better form an inorganic salt structure or film on the surface of the positive electrode sheet 110 or the negative electrode sheet 130, thereby reducing the impedance of the positive electrode sheet 110 or the negative electrode sheet 130, and better improving the dynamic performance of the positive electrode sheet 110 or the negative electrode sheet 130. For example, lithium difluorophosphate can form an inorganic salt structure such as lithium fluoride on the negative electrode sheet 130, which can reduce the impedance of the negative electrode sheet 130 and improve the dynamic performance of the negative electrode sheet 130. For another example, lithium difluorooxalatoborate can form a film on the surface of the positive electrode sheet 110 and the negative electrode sheet 130 , thereby reducing the impedance of the positive electrode sheet 110 and the negative electrode sheet 130 and improving the dynamic performance of the positive electrode sheet 110 and the negative electrode sheet 130 .

[0163] Optionally, the electrolyte also includes an organic solvent. The organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Cyclic carbonates have a high dielectric constant and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode plate 130, but their viscosity is relatively large. Chain carbonates have lower viscosity than cyclic carbonates, better electrochemical stability, and can improve the low-temperature performance of the electrolyte. Therefore, when a mixed solvent of cyclic carbonate and chain carbonate is used, the electrolyte can have a more suitable viscosity and low-temperature stability, and the battery 100 using the electrolyte can be better film-formed.

[0164] Optionally, the cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC for short), propylene carbonate (PC for short), etc. The dielectric constant of ethylene carbonate is much greater than that of propylene carbonate, and ethylene carbonate can better promote the formation of SEI film.

[0165] Optionally, the linear carbonate may include but is not limited to at least one of dimethyl carbonate (DMC for short), diethyl carbonate (DEC for short), ethyl methyl carbonate (EMC for short), and the like.

[0166] Optionally, in the electrolyte, the mass fraction of the organic solvent is 60wt% to 85wt%, specifically, but not limited to, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc.

[0167] Optionally, the organic solvent further comprises at least one of ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, γ-butyrolactone, and 2,2-difluoroethyl acetate.

[0168] The electrolyte and the battery 100 of the present application are further described below through specific embodiments.

[0169] Examples 1 to 26 and Comparative Example 1

[0170] The preparation method of the battery 100 of each embodiment and comparative example includes:

[0171] (1) Preparation of positive electrode sheet 110: The positive electrode active material lithium iron phosphate (LiFePO4), conductive carbon black (positive electrode conductive agent, Super-P), and adhesive (positive electrode binder, PVDF) are dispersed in N-methylpyrrolidone (NMP) solvent according to a preset mass ratio, mixed evenly and prepared into a positive electrode slurry with a solid content of 60%; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector 111 aluminum foil with a thickness of 10 μm, and the coating weight of the positive electrode slurry is 300 mg / 1540.25 mm 2 After drying, cold pressing, slitting and cutting, the positive electrode slurry is solidified to form a positive electrode active layer 112, and a positive electrode sheet 110 is obtained, wherein the thickness of a single side of the positive electrode active layer 112 is 100 μm;

[0172] (2) Preparation of negative electrode sheet 130: Graphite (negative electrode active material), sodium carboxymethyl cellulose (negative electrode thickener, referred to as CMC), styrene butadiene rubber latex (negative electrode binder SBR), and asphalt are dispersed in deionized water according to a preset mass ratio and prepared into a negative electrode slurry with a solid content of 50%. The negative electrode slurry is evenly coated on a copper foil of the negative electrode current collector 131 with a thickness of 6 μm. The coating weight of the negative electrode slurry is 144 mg / 1540.25 mm 2 After drying, cold pressing, slitting and cutting, the negative electrode slurry is solidified to form a negative electrode active layer 132, and a negative electrode sheet 130 is obtained, wherein the thickness of a single side of the negative electrode active layer 132 is 70 μm;

[0173] (3) Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1 ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1 to obtain a mixed solvent, and then dry electrolyte salt lithium hexafluorophosphate is dissolved in the mixed solvent, stirred until completely dissolved and uniformly dissolved, and an azaindole additive is added, and stirred uniformly to obtain an electrolyte, wherein the molar concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L, and the types and addition amounts of the azaindole additives in each of Examples 1 to Example 26 and Comparative Example 1 are shown in Table 1 below;

[0174] (4) Preparation of the separator 120 : A 16 μm polyethylene film was used as the separator 120 .

[0175] (5) Assembly of battery 100: The positive electrode sheet 110, the separator 120, and the negative electrode sheet 130 are stacked in sequence to form an electrode assembly, and the electrode assembly is wound to obtain a bare cell. After welding the tabs, the cell is assembled into an outer package, and after injecting the above-mentioned electrolyte, vacuum packaging, standing, forming, shaping, capacity testing, etc. are performed to finally prepare battery 100.

[0176] The performance test was performed on the battery 100 of each embodiment and comparative example:

[0177] (1) 45℃ cycle performance test: Under 45℃ environment, let the initialized battery 100 stand for 5h; charge to 3.65V at 1P constant power, let stand for 10 minutes; discharge to 2.5V at 1P constant power, let stand for 10 minutes; such a charge-discharge process is called a cycle process or a cycle. 1P constant power charging / 1P constant power discharging is used to test the cycle performance of the battery 100, record the discharge capacity of the battery 100 after 1000 cycles, and calculate the cycle capacity retention rate of the battery 100 after 1000 cycles. Cycle capacity retention rate = (discharge capacity of the 1000th cycle / initial discharge capacity C0) × 100%.

[0178] The initial discharge capacity percentage of the battery 100 of each of Examples 1 to 26 and Comparative Example 1 and the cycle capacity retention rate after 1000 cycles at 45° C. and a charge and discharge rate of 1P are shown in Table 1 below.

[0179] Table 1 Performance parameters of the battery 100 of Examples 1 to 26 and Comparative Example 1

[0180]

[0181]

[0182] It can be seen from the test data of Comparative Example 1 that when no azaindole additive is added to the electrolyte, the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C is low. This may be because during the charge and discharge cycle of the battery 100, as the electrochemical process of charging and discharging the battery 100 is accompanied by the expansion and contraction process of the SEI film, at this time, the SEI film has poor cycle stability at high temperature, so the SEI film is constantly destroyed and repaired, and the process of generating the SEI film is the process of the electrolyte components gaining and losing electrons on the surface of the negative electrode active layer 132, which is accompanied by the loss of active lithium, and it is an irreversible loss. The reduction in the active lithium content leads to the deterioration of the charge and discharge cycle capacity of the battery 100.

[0183] It can be seen from the test data of Examples 1 to 8 that when azaindole additives are added to the electrolyte, the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C can be improved. When the amount of azaindole additives added to the electrolyte is small (such as Example 1), the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C is improved less; as the content of azaindole additives in the electrolyte increases, the cycle capacity retention of the battery 100 after 1000 cycles at 45°C first gradually increases and then gradually decreases. This may be because when the content of azaindole additives in the electrolyte is too high, the thickness of the SEI film formed on the surface of the negative electrode plate 130 is too thick, which reduces the kinetic performance of the battery 100, making it easy for the battery 100 to precipitate lithium during the charge and discharge cycle, consuming active lithium, and in addition, it will increase the polarization of the battery 100, causing the loss of reversible lithium, thereby reducing the cycle performance of the battery 100. When the amount of the azaindole additive added to the electrolyte is 0.1% to 3%, the battery 100 has a higher high temperature cycle capacity retention rate. Further, when the amount of the azaindole additive added to the electrolyte is 0.3% to 1%, the battery 100 has an even higher high temperature cycle capacity retention rate.

[0184] It can be seen from the test results of Examples 1 to 26 that adding different azaindole additives to the electrolyte can significantly improve the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C.

[0185] From the test data of Example 5, Example 10, Example 13, Example 16, Example 19, Example 22, Example 24 to Example 26, it can be seen that when the amount of azaindole additives added is the same, compared with 4-azaindole (Example 24), 5-azaindole (Example 25) and 6-azaindole (Example 26), when 7-azaindole additives are added to the electrolyte, the effect of improving the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C is more obvious. That is, the addition of 7-azaindole additives can better improve the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C. This is because 7-azaindole has a stronger coordination ability than azaindole, and can easily participate in Li + The solvated structure is more likely to migrate to the surface of the negative electrode active layer 132 to undergo a reduction reaction; furthermore, the SEI interface film constructed by 7-azaindole can reduce the side reactions at the SEI interface during the cycle process and reduce the consumption of active lithium, thereby further improving the cycle performance of the battery 100.

[0186] In addition, from Example 5, Example 10, Example 13, Example 16, Example 19 and Example 22, when the amount of 7-azaindole additive added is the same, the introduction of fluorine-containing groups (electron-withdrawing groups), silicon-containing groups and reactive groups at the 5-position of the 7-azaindole additive can better improve the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C. This is because the fluorine-containing group can reduce the lowest unoccupied molecular orbital (LUMO energy level) of the azaindole additive, thereby increasing the reduction potential of the azaindole additive, so that the azaindole additive preferentially reacts at the cross section of the negative electrode active layer 132 and participates in the construction of the SEI film; in addition, the azaindole additive containing fluorine substituents can increase the LiF component in the SEI film, thereby further reducing the solubility of the SEI film in the electrolyte, improving the thermal stability and acid resistance of the SEI film, and thus improving the high temperature cycle performance of the battery 100. The silicon-containing azaindole additive can react with HF in the electrolyte to remove free acid in the electrolyte, thereby preventing the free acid from damaging the SEI film, improving the stability of the SEI film, and thus improving the high-temperature cycle performance of the battery 100. The reactive group can participate in the reaction of the SEI film, increase the degree of polymerization of the organic components in the SEI film, so that the organic components in the SEI film can withstand higher temperatures, thereby improving the thermal stability of the SEI film, reducing the solubility of the SEI film in the electrolyte, and improving the cycle performance of the battery 100.

[0187] Example 27 to Example 41, Comparative Example 2 to Comparative Example 5

[0188] The difference between Examples 27 to 41 and Comparative Examples 2 to 5 and Example 3 is that the electrolyte includes a first additive and a second additive. The types and contents of the first additive and the second additive in the electrolytes of Examples 27 to 41 and Comparative Examples 2 to 5 are specifically shown in Table 2 below.

[0189] Table 2 Performance parameters of the battery 100 of Examples 27 to 41 and Comparative Examples 2 to 5

[0190]

[0191] It can be seen from the test results of Example 6, Example 27 and Comparative Example 2 that, compared with the solution of adding only azaindole additives to the electrolyte (such as Example 6) and adding only vinylene carbonate additives (VC, such as Comparative Example 2), when the content of the additives is the same, adding both azaindole additives and vinylene carbonate additives to the electrolyte (Example 27) can better improve the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C. This is because when the azaindole additives and the vinylene carbonate additives are used in combination, the azaindole additives can copolymerize with the vinylene carbonate additives and promote the ring-opening reaction of the vinylene carbonate additives, further generate inorganic salts and organic polymers, improve the thermal stability of SEI, and thus further improve the cycle performance of the battery 100.

[0192] It can be seen from the test results of Examples 27 to 30 that when the content of the azaindole additive in the electrolyte remains unchanged, as the content of the vinyl carbonate additive in the electrolyte increases, the cycle capacity of the battery 100 after 1000 cycles at 45°C first increases and then decreases.

[0193] It can be seen from the test results of Example 6, Example 31 and Comparative Example 3 that, compared with the solution of adding only azaindole additives to the electrolyte (such as Example 6) and adding only vinyl sulfate additives (VC, such as Comparative Example 3), when the content of the additives is the same, adding both azaindole additives and vinyl sulfate additives to the electrolyte (Example 31) can better improve the cycle capacity retention rate of the battery 100 after 1000 cycles at 45°C. This is because when the azaindole additives and the vinyl sulfate additives are used in combination, the addition of the azaindole additives can promote the ring-opening reaction of the vinyl sulfate additive, further generate inorganic salts and organic polymers, improve the thermal stability of the SEI, and thus further improve the cycle performance of the battery 100.

[0194] It can be seen from the test results of Examples 31 to 34 that when the content of the azaindole additive in the electrolyte remains unchanged, as the content of the vinyl sulfate additive in the electrolyte increases, the cycle capacity of the battery 100 after 1000 cycles at 45°C first increases and then decreases.

[0195] In addition, from the test results of Example 28 and Example 32 (or Example 29 and Example 33, or Example 30 and Example 34), it can be seen that compared with the solution of compounding azaindole additives with vinyl sulfate additives, compounding azaindole additives with vinyl carbonate additives can better improve the cycle capacity retention rate of battery 100 after 1000 cycles at 45°C.

[0196] From the test results of Example 29, Example 35 to Example 41, it can be seen that as the ratio of 7-azaindole to vinylene carbonate in the electrolyte increases, the cycle capacity retention of the battery 100 after 1000 cycles at 45° C. first increases and then decreases. When the ratio of 7-azaindole to vinylene carbonate is between 0.1 and 1.5, the cycle capacity retention rate of the battery 100 after 1000 cycles at 45° C. is high. This is because when the mass ratio A of the first additive to the second additive is too small, the content of the azaindole additive in the electrolyte is too little, and the content of nitrogen in the SEI film of the negative active layer 132 is insufficient, which reduces the thermal stability of the SEI film, thereby deteriorating the high temperature cycle performance of the battery 100, causing the cycle capacity retention rate of the battery 100 to decrease after 1000 cycles at 45°C; when the mass ratio A of the first additive to the second additive is too large, the SEI film of the negative active layer 132 is mainly constructed by the azaindole additive, the polymer of the organic layer in the SEI film is reduced, and it is difficult to form a dense and thick SEI film, which makes the SEI film easily damaged, thereby causing the cycle capacity retention rate of the battery 100 to decrease after 1000 cycles at 45°C. When the mass ratio A of the first additive to the second additive is 0.1 to 1.5, when the SEI membrane of the battery 100 is constructed, the azaindoles preferentially undergo a reduction reaction, promoting the polymerization reaction of the cyclic carbonate additive, and forming an organic layer of the SEI membrane with a high degree of polymerization with the cyclic carbonate additive, thereby improving the thermal stability of the SEI and the high-temperature cycle performance of the battery 100.

[0197] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0198] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes an electrolyte salt and a first additive, wherein the first additive is an azaindole additive.

2. The electrolyte according to claim 1, characterized in that The azaindole additive comprises at least one of the following structural formulas: Wherein, R1 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R2 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R3 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R4 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R5 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R6 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R7 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R8 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R9 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 10 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 11 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 12 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 13 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 14 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 15 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 16 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 17 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 18 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 19 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 20 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 21 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 22 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 23 is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl, and vinyl; R 24 It is at least one of hydrogen, fluorine, methyl, trifluoromethyl, trimethylsilyl and vinyl.

3. The electrolyte according to claim 1, characterized in that The azaindole additive has a substituent, and the substituent includes at least one of an electron-withdrawing group, a silicon-containing group, and a reactive group.

4. The electrolyte according to claim 1, characterized in that The azaindole additive comprises at least one of the following structural formulas:

5. The electrolyte according to claim 1, characterized in that The electrolyte further includes a second additive, and the second additive includes at least one of a cyclic carbonate additive and a cyclic sulfate additive.

6. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass ratio A of the first additive to the second additive is in the range of 0.1≤A≤1.

5.

7. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction a of the first additive is in the range of 0.05%≤a≤3.0%.

8. The electrolyte according to claim 5, characterized in that In the electrolyte, the mass fraction b of the second additive is in the range of 1%≤b≤4%.

9. A battery, characterized in that: include: The electrolyte according to any one of claims 1 to 8; A positive electrode sheet, the positive electrode sheet is immersed in the electrolyte; a diaphragm, located on one side of the positive electrode plate and immersed in the electrolyte, and A negative electrode plate is disposed on a side of the diaphragm away from the positive electrode plate and immersed in the electrolyte.

10. An energy storage device, characterized in that: include: Box; as well as A plurality of batteries as claimed in claim 9, wherein the plurality of batteries are housed in the casing.

11. An energy storage system, characterized in that: include: The energy storage device according to claim 10; as well as An electric energy conversion device, wherein the electric energy conversion device is electrically connected to the energy storage device, the electric energy conversion device is used to convert other forms of energy into electric energy, and the energy storage device is used to store the electric energy.

Citation Information

Patent Citations

  • Acid-scavenging functional separators for power performance of lithium ion electrochemical cells

    CN109148796A

  • Positive and reverse pulse electrolytic nickel-tungsten alloy solution, preparation method, electroplating method and nickel-tungsten alloy coating

    CN115976586A

  • Electrolyte, battery and power utilization system

    CN117712487A

  • Electrolyte, battery, energy storage device and energy storage system

    CN118841628A

  • Lithium polymer battery

    JP2009070605A